Agential black body in Jesmyn Ward’s Sing, Unburied, Sing - Wan Fang,; Mohammad Ewan Awang,; Noritah Omar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Jesmyn Ward’s novel Sing, Unburied, Sing (2017) vividly captures the lived experiences of African Americans in the rural Southern United States amidst the enduring legacies of slavery and the ongoing impact of racial subjugation. This article focuses on the novel’s portrayal of its Black characters and articulation of the Black body to demonstrate how the Black body not only bears the scars of systemic, historical-social injustice but also functions as a site of recuperation. Building upon George Yancy’s concept of “the agential Black body”, the article contends that affirming the Black body requires acknowledging the epistemic violence imposed upon it and recognising the body’s potential to transcend such limitations. Yancy’s concept of Black affirmation and modalities of Black ontology, including storytelling and musicking, are especially relevant in this article’s analysis of Ward’s Sing, Unburied, Sing. These elements illustrate how, in the novel, the Black body—through embodied self-articulation—testifies to moments of violation and uses those moments to re-inscribe itself. Thus, the Black body expands beyond the limited and essentialist (white) configurations, and gestures towards its state of possibilities. The article argues that the novel’s narrative techniques and its engagement with African American literary traditions re-visibilise and manifest the resilience of the Black body.